The association between death anxiety and nutrition awareness in elderly hospitalized patients: a dual-perspective analysis from person-centered and variable-centered approaches based on future time perspective - Li, Lijun; Wu, Dan; He, Qin; Chen, Jianao (Frontiers in Nutrition, 2026)
BackgroundWith the acceleration of global population aging, psychological health issues among elderly hospitalized patients have become increasingly prominent. Death anxiety, as a key psychological experience of existential threat, is associated with psychological adaptation challenges in older adults and may be related to health behavior intentions. Nutrition awareness is a critical factor in promoting rehabilitation and healthy aging; however, the associations between death anxiety and nutrition awareness, as well as potential psychological pathways, remain understudied.ObjectiveThis study aims to examine the associations among death anxiety, future time perspective, and nutrition awareness, while identifying group heterogeneity through latent profile analysis.MethodsThis study employed a cross-sectional design, recruiting elderly hospitalized patients (N = 557) from three tertiary Grade-A hospitals in Hangzhou and Chongqing, China. Measurements were conducted using the Death Anxiety Scale, Future Time Perspective Scale, and Nutrition Awareness Scale. Data analyses included descriptive statistics, correlation analysis, structural equation modeling, and latent profile analysis.ResultsDeath anxiety was significantly and positively associated with both future time perspective and nutrition awareness. Future time perspective demonstrated a significant indirect effect in the relationship between death anxiety and nutrition awareness, suggesting a partial mediation pattern. Latent profile analysis identified three distinct subgroups: “low death anxiety–low future time perspective,” “moderate death anxiety–moderate future time perspective,” and “high death anxiety–high future time perspective,” with the latter group demonstrating the highest levels of nutrition awareness.ConclusionUnder the moderating influence of future time perspective, death anxiety can be transformed into a positive psychological driver for health-promoting behaviors. Enhancing future orientation and sense of life meaning in elderly patients can convert anxious emotions into motivation for health management, providing a scientific basis for individualized psychological-nutritional interventions.